2020
DOI: 10.1590/0034-761220190020
|View full text |Cite
|
Sign up to set email alerts
|

Nomeações políticas nos governos municipais e performance burocrática: avaliando o desempenho

Abstract: Resumo Este artigo aborda a politização das estruturas burocráticas dos municípios brasileiros mediante cargos comissionados (CCs). Os dados foram obtidos por meio do banco de dados do grupo de pesquisa Instituições Políticas Comparadas (IpoC), do Instituto Brasileiro de Geografia e Estatística (IBGE), e dos sites oficiais do Conselho Federal de Administração (CFA) e da Federação das Indústrias do Rio de Janeiro (FIRJAN). Inicialmente, verificou-se o grau de variabilidade da distribuição desses cargos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…However, there are also studies that have not clearly identified this relationship (Cardoso and Marenco, 2020) and show that there are no losses in the performance of organizations as a result of political appointments (Fonseca, 2019). This reinforces the fact that patronage is not restricted to clientelist intentions or to reward Allies, but also as a legitimate search for greater governability and control of public policies, which allows the government's interest agendas to be prioritized (Chudnovsky, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are also studies that have not clearly identified this relationship (Cardoso and Marenco, 2020) and show that there are no losses in the performance of organizations as a result of political appointments (Fonseca, 2019). This reinforces the fact that patronage is not restricted to clientelist intentions or to reward Allies, but also as a legitimate search for greater governability and control of public policies, which allows the government's interest agendas to be prioritized (Chudnovsky, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Although focusing on clientelism and using the categories 'legislator ' , 'fundraiser' and 'assistentialist' , Lopez and Almeida (2017) revealed that the probability that councilmen prioritize meeting particular demands increases with electoral competition, but decreases in large municipalities and with higher electoral volatility. Cardoso and Marenco (2020) studied the relationships between political appointments and municipal performance, and showed the need to develop cut-offs to better capture these links. Several papers have already considered schooling as one of the dimensions to explain municipal and state capacity (Batista, 2015;Batista, Rocha, & Santos, 2020;Cardoso & Marenco, 2019;Marenco, 2017;Marenco & Strohschoen, 2018;Marenco, Stroeschen, & Joner, 2017).…”
Section: Policitization Political Appointments and Patronagementioning
confidence: 99%
“…Este trabalho insere-se em uma geração de novas investigações sobre municípios e governos locais, que tem apresentados achados sobre variações em capacidades estatais nas administrações municipais (Grin & Abrucio, 2018;Grin & Abrucio, 2019;Marenco, 2017;Marenco, Stroeschoen & Joner, 2017;Cardoso & Marenco, 2020), no planejamento governamental (Lima et al, 2020), qualidade de gestão e desempenho fiscal (Karruz & Moraes, 2020, Aranha, 2019, indicadores de desenvolvimento humano (Coelho, Guth & Loureiro, 2020), na implementação de programas federais (Grin, 2014, Batista, 2015, em transparência e corrupção (Batista, Rocha & Santos, 2020), no enfrentamento a pandemia (Batista, 2020;Grin, 2020).…”
Section: Contribuições Deste Trabalhounclassified